2006
DOI: 10.1309/afha406gbt0n2y64
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Ulcerative Granuloma With Stromal Eosinophilia

Abstract: Traumatic ulcerative granuloma with stromal eosinophilia (TUGSE) is a benign lesion of the oral mucosa of an unclear pathogenesis. We analyzed the profile of the inflammatory infiltrate in 12 cases of TUGSE by using immunohistochemical analysis and polymerase chain reaction-based repertoire analysis to detect T- and B-cell receptor gene rearrangements. The inflammatory infiltrate consisted in most cases of B and T lymphocytes, macrophages, abundant eosinophils, and large atypical cells. In 5 cases, CD30+ cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 36 publications
2
49
2
Order By: Relevance
“…Constituents of eosinophil secretory granules include a number of highly cytotoxic proteins, such as eosinophilic cationic protein, major basic protein and eosinophil-derived neurotoxin. Immunohistochemical studies demonstrated that the atypical mononuclear cells are atypical large CD30+ T cells with polymorphic convoluted nuclei and prominent nucleoli [33,34]. In our case, no CD8+ cells were found, but perforin was expressed by CD30+ cells which may be, together with eosinophilic cytokines, responsible for the ulceration.…”
Section: Discussion and Reviewmentioning
confidence: 54%
See 1 more Smart Citation
“…Constituents of eosinophil secretory granules include a number of highly cytotoxic proteins, such as eosinophilic cationic protein, major basic protein and eosinophil-derived neurotoxin. Immunohistochemical studies demonstrated that the atypical mononuclear cells are atypical large CD30+ T cells with polymorphic convoluted nuclei and prominent nucleoli [33,34]. In our case, no CD8+ cells were found, but perforin was expressed by CD30+ cells which may be, together with eosinophilic cytokines, responsible for the ulceration.…”
Section: Discussion and Reviewmentioning
confidence: 54%
“…Trauma has been suggested to play a major role as previously mentioned, albeit widely regarded as a factor initiating a hypersensitive T cell-mediated immune response to altered tissue antigens or unknown factors (e.g. viral particles, toxic microbial products) [15,34]. Likewise, increased stromal mast cell infiltration has been reported [15], a finding that was not confirmed by others [8].…”
Section: Discussion and Reviewmentioning
confidence: 99%
“…Abraham et al . [1] found in his study a positivity for marker of cytotoxic T cell activity in all his cases, supporting the role of cytotoxic T cells in the pathogenesis of TUGSE.…”
mentioning
confidence: 60%
“…TUGSE can occur anywhere in the oral cavity, and the most common sites include the ventral surface of the tongue, buccal mucosa, vestibule and floor of the mouth. [1] Although it usually follows some form of trauma, most patients do not have a history of trauma. Most commonly, the lesion presents as a self-healing solitary ulcer with rolled up or indurated margins of weeks to months duration.…”
mentioning
confidence: 99%
“…The characteristic features of these conditions are detailed in Table 3 [41][42][43][44][45]. The diagnosis of PG is primarily based on recognition of the characteristic morphology and evolution of the lesion, the presence of an underlying systemic disease (if any) and, the exclusion of other disease processes using proper diagnostic tools.…”
Section: Differential Diagnosismentioning
confidence: 99%